Influence of awake bruxism behaviors on fatigue of the masticatory muscles in healthy young adults - Maria Isabel BARRAGÁN NUÑEZ; Dyanne Medina FLORES; Giancarlo DE LA TORRE CANALES; Henrique Müller de QUEVEDO; Paulo Rodrigues CONTI; Yuri Martins COSTA; Leonardo Rigoldi BONJARDIM (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The present cross-sectional study aimed to analyze the relationship between awake bruxism and fatigue of masticatory muscles in healthy young adults. For this purpose, 121 graduate students participated in this study. Frequency of awake bruxism was collected for 7 consecutive days by ecological momentary assessment (EMA) using an online survey (mentimeter). Muscle fatigue was tested one day after EMA assessment, which consisted of voluntarily and continuously clenching at 30% (kgf/cm2) of maximum bite force (MBF) until exhaustion. The percentage of change in MBF after the clenching task, as compared to the MBF before the clenching task was measured. The average frequency of awake bruxism was 45.5% during 7 days. Sustained clenching resulted in a significant reduction in MBF values in the total sample (p < 0.05). Nevertheless, no significant correlation was found between frequency of awake bruxism behaviors and percent of change in MBF and endurance time during the fatigue test. Therefore, it can be concluded that young healthy adults present a relatively high frequency of awake bruxism behaviors that do not seem to impact the degree of masticatory muscle fatigue.